PENGGANTIAN RUMPUT GAJAH DENGAN JERAMI PADI SEBAGAI SUMBER ENERGI YANG DISUPLEMENTASI DAUN GAMAL SEBAGAI SUMBER RUMEN DEGRADABLE PROTEIN (RDP) TERHADAP KOMPOSISI TUBUH SAPI BALI - Widiadnyana, I M. Adi; Suryani, N. N.; Astawa, I P. A. (Jurnal Peternakan Tropika; Volume 1 No. 2 Tahun 2013)
The study is titled replacement elephant grass with rice straw as an energy source supplemented Gliricidia leaves as a source of Rumen Degradable Protein (RDP) on body composition Bali cattle. The experiment was conducted in groups of cattle Wibuh Mandiri, banjo Tangkeban Batuyang Kangin village, Sukawati, Gianyar district, conducted over 12 weeks from 22 July 2011 until 14 October 2011. The design used was a randomized block design (RBD) consisting of 4 treatment diets with three weight groups as replicates. Variables measured were body composition, ie body water content, body fat, body protein and fat retention. Body composition was determined by means of urea space (Rule et al ., 1986). The results showed that the replacement of grass with rice straw as a source of energy up to 30% with 30% leaf suplentasi gamal, does not give a significant effect on body water content, protein content of the body and body fat content of Bali cattle. The higher content of rice straw and Gliricidia leaves ration causes increased fat retention
Keywords: Elephant Grass, Rice Straw, Gliricidia Leaves Body Composition, Bali Cattle